(untitled) (Anclajes, 2012)
At the end of the nineteenth century, two antagonistic factions disputed the hegemony of the Spanish intellectual field: the orthodox Catholic traditionalism and the Krausist liberalism. In such a significant context, to look for evidences of the theoretical confrontation between Marcelino Menéndez y Pelayo and Manuel de la Revilla acquires real importance when trying to understand the origin of opposing viewpoints between the Hispanic critics. Besides, the readings made by Menéndez y Pelayo and Alcántara García on Lope de Vega’s Arte nuevo helps to illustrate the subject by means of an example with precise resonances.